1988
DOI: 10.2118/14161-pa
|View full text |Cite
|
Sign up to set email alerts
|

Gravel Placement Through Perforations and Perforation Cleaning for Gravel Packing

Abstract: Gravel Placement Through Perforations and Perforation Cleaning Perforations and Perforation Cleaning for Gravel Packing Summary. In large-scale model testing, the effectiveness of gravel prepacking under four different conditions was studied: when there had been prepacking under four different conditions was studied: when there had been no previous sand production, after sand production had occurred, after perforation washing, and after perforation surging. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The perforating objective is to obtain debris-free perforation tunnels that can be filled with sand during the sand control process. 1,2,3 The desired results are to obtain high-density perforation tunnels with large cross sectional areas and minimum flow restriction. Underbalanced perforating with TCP guns has proven to be the most effective method for obtaining the desired cleanliness in perforation tunnels.…”
Section: Perforatingmentioning
confidence: 99%
See 2 more Smart Citations
“…The perforating objective is to obtain debris-free perforation tunnels that can be filled with sand during the sand control process. 1,2,3 The desired results are to obtain high-density perforation tunnels with large cross sectional areas and minimum flow restriction. Underbalanced perforating with TCP guns has proven to be the most effective method for obtaining the desired cleanliness in perforation tunnels.…”
Section: Perforatingmentioning
confidence: 99%
“…8). 3. During the perforating process, a unrestricted flow path must be maintained through the gravelpack assembly (Fig.…”
Section: Gravelpack Packer Assembly Operational Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods, in combination with flow surges, aid in removing plugging material, formation sand, and gun debris so that highly permeable gravelpack sand can be placed in the perforations. 7 Underbalanced tubing-conveyed-perforating (TCP) techniques were used exclusively at Xijiang, as previous studies indicated that underbalanced perforating with tubing-conveyed guns has yielded better results than perforation washing or surging after perforating. 8 TCP guns were 7-in.-outside-diameter (OD) expendable hollow carriers with 56.5-g big-hole, low-debris charges phased at 72°.…”
Section: Perforatingmentioning
confidence: 99%
“…The importance of packing the perforations is critical to gravel-pack productivity and completion longevity. 12,13 Consequently, field procedures have been developed to ensure that the perforations are effectively packed with gravel. 14, 15 Although wells have been gravel packed with a wide variety of procedures and techniques, misunderstandings abound concerning the transport phenomena involved with gravel placement in wells because water and viscous fluids have been used to place gravel.…”
Section: Introductionmentioning
confidence: 99%